PENERAPAN PEMBELAJARAN TERPADU PADA PROSES PEMBELAJARAN VOKASIONAL DI PROGRAM STUDI PENERBITAN POLITEKNIK NEGERI MEDIA KREATIF JAKARTA - Astuti, Irene Maria Juli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2015)
Vocational learning is designed to produce graduation that are ready to enter the workforce requirements. One thing that should be taken into consideration is the curriculum implementation where the class theory covers 40% and industrial practice covers 60 % of the framework remaining. The practical activities from various subjects needs to be integrated to achieve a continuous and meaningful learning result. Integrated learning is a learning methodology where some competencies are integrated and has to be achieved from various subjects approach through one interconnected and continuous assignment. The purpose of this research is to describe the integration process from Writing, Editing and Publishing Marketing in one learning continuum. Methodology used in this research is a case study using the students of “Politeknik Negeri Media Kreatif ‘publishing class semester four as the source of data. The result of this research is the complete description of the integrated learning equipped with the syllabus and the lesson plan for Writing, editing and Publishing Marketing subject. The conclusion of this research is integrated learning overcome the overlaps topics and resulted on a holistic, continuous and meaningful learning outcomes.